Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Liny Jaya Informatika Makassar - Andi Irfan; Aminah Aminah; Claudya Armelia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of work motivation on employee performance. The object of this research is PT. Liny Jaya Informatics Makassar which operates in the field of science and technology. The data used in this research is primary data with a sampling method using purposive sampling, and a data analysis method using simple regression analysis, while the sample taken was 40 employees. The results of this research have been tested for validity and reliability, and hypothesis testing has also been carried out using simple regression analysis techniques. The results of this research show that the work motivation variable (X) has a positive and significant effect simultaneously on employee performance (Y), meaning that if work motivation increases, employee performance will increase.